STRATEGI PEMASARAN PAKET WISATA TIRTAYATRA KE INDIA PADA MELATI TOURS - Gede Jelantik, Kadek Bagus; Wijaya, N.M.S.; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021)DO - 10.24843/IPTA.2021.v09.i01.p18, 2021)
Many travel agents facilitate the interest of tourists, especially Balinese people to do Tirtayatra to India. One of them is Melati Tours as a travel agent providing package tours of Tirtayatra to India. This study was conducted to find out the right marketing strategy of Tirtayatra tour packages to India at Melati Tours. The data analysis technique used are internal environment/IFAS using Marketing Mix 7P analysis as an internal factors and external environment/EFAS using market analysis, competitor analysis, government analysis, technology analysis, economic analysis, social-cultural analysis, environmental analysis and SWOT analysis. The type of data used is quantitative and qualitative data, primary and secondary data. Data collection techniques by observation, interviews, study of literature, documentation and distribution of external internal questionnaires to 100 tourist who bought Tirtayatra tour packages at Melati Tours and to Melati Tours owners and Tourism Academics. Data analysis technique used is mix methods. This study used 18 internal sub-indicators and 8 external sub-indicators and obtained 11 strength factors, 7 weakness factors, 5 opportunity factors and 3 threat factors. Based on the results of data processing on external internal factors/IFAS EFAS, the total value of IFAS is 2,65 and EFAS is 2,20, this indicating the position of the Tirtayatra tour package on Melati Tours in this study is in cell VIII, namely Growth Strategy and Conglomerate Diversification. Melati Tours in marketing Tirtayatra tour packages to India requires a growth strategy through more strategic pressure on financial synergy rather than product marketing strategy for products and prices balance.